Gut microbiota-modulating agents in alcoholic liver disease: Links between host metabolism and gut microbiota - Jung, Jang Han; Kim, Sung-Eun; Suk, Ki Tae; Kim, Dong Joon (Frontiers in Medicine, 2022)
Alcoholic liver disease (ALD) involves a wide spectrum of diseases, including asymptomatic hepatic steatosis, alcoholic hepatitis, hepatic fibrosis, and cirrhosis, which leads to morbidity and mortality and is responsible for 0.9% of global deaths. Alcohol consumption induces bacterial translocation and alteration of the gut microbiota composition. These changes in gut microbiota aggravate hepatic inflammation and fibrosis. Alteration of the gut microbiota leads to a weakened gut barrier and changes host immunity and metabolic function, especially related to bile acid metabolism. Modulation and treatment for the gut microbiota in ALD has been studied using probiotics, prebiotics, synbiotics, and fecal microbial transplantation with meaningful results. In this review, we focused on the interaction between alcohol and gut dysbiosis in ALD. Additionally, treatment approaches for gut dysbiosis, such as abstinence, diet, pro-, pre-, and synbiotics, antibiotics, and fecal microbial transplantation, are covered here under ALD. However, further research through human clinical trials is warranted to evaluate the appropriate gut microbiota-modulating agents for each condition related to ALD.